2021
DOI: 10.3390/su13116283
|View full text |Cite
|
Sign up to set email alerts
|

The Study of AR-Based Learning for Natural Science Inquiry Activities in Taiwan’s Elementary School from the Perspective of Sustainable Development

Abstract: Experiential activities are the most direct form of ecological teaching, so outdoor education is an important way of learning. Through direct observation and life experience, students will learn about the ecological environment, understand the importance of the ecological environment, raise their awareness of environmental protection, and put into practice the protection of the ecological environment. This study involved plant teaching activities that incorporated school plant learning paths into environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…That is, older students tended to think that AR applications were not very useful. It was hypothesized by the authors that the older the students were, the harder it was for them to follow the teacher's instructions, or the more difficult for them to learn [56]. Shin (ID55) found that the learners did not enjoy the experience of desktop VR, because it did not generate a strong sense of immersion [57].…”
Section: Affective Goalsmentioning
confidence: 99%
“…That is, older students tended to think that AR applications were not very useful. It was hypothesized by the authors that the older the students were, the harder it was for them to follow the teacher's instructions, or the more difficult for them to learn [56]. Shin (ID55) found that the learners did not enjoy the experience of desktop VR, because it did not generate a strong sense of immersion [57].…”
Section: Affective Goalsmentioning
confidence: 99%
“…Spatial visualization can reduce students' cognitive load while working on assignments. One of the new technologies that can visualize learning is Augmented Reality, a new technology that is easy to use and relevant to adapt (Anuar et al, 2021;Lo et al, 2021). One of the learning media trends that have become a concern in education is media with Augmented Reality (AR) technology (Hincapie et al, 2021;Yavuz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of the important factors that could support the success of the science learning process in elementary schools is the selection of learning approaches (Century et al, 2020;Huang et al, 2020). By the presence of appropriate learning approach, especially in science learning, it would be able to optimize learning outcomes because approach applied by teachers to the learning process is one of the external factors that could affect students' learning outcomes (Kumala et al, 2020;Lo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%